Peningkatan keterampilan menulis aksara jawa melalui model pembelajaran think talk write berbantuan media teka-teki silang - Mohamad Aziz Aridho; Suharno Suharno; Joko Daryanto (Universitas Sebelas Maret, 2019)
The lead up of research design is upgrade Javanese-script writing skills by applying Cooperative Learning Model of Crossword Puzzle media-mixed Think Talk Write model. Classroom Action Research with two cycles is used in this research. Subject of research belongs to student in Grade V of Public Elementary School 01 of Logede, Pejagoan, Kebumen in 2018-2019 academic year amount 22 students. The research utilizes the data collection techniques through observations, in-depth interviews, testing, and documentations by applying analyis of content validity, technique triangulation, and source triangutation. The data were processed by taking interactive analysis model of Miles and Huberman.The outcome shows that the initial condition of Javanese script writing skill in grade V is 4,55% classical. Then, the practice of Cooperative Learning Model of Crossword Puzzle media-mixed TTW model, it make 12 out o 22 (54,55%) in cycle 1 and 20 out of 22 (90,90%) in cycle 2. So, aplication of Cooperative Learning Model of Crossword Puzzle-mixed Think Talk Write model can jack-up Javanese-script writing skills in Grade V of Public Elementary School 01 of Logede, Pejagoan, Kebumen